NURSE-LED PREDICTIVE PERFORMANCE OF INTEGRATED PEWS–TRIAGE SYSTEMS IN PEDIATRIC EMERGENCY DETECTION - Citra Suraya; Aris Citra Wisuda; Rinda Suciarti (Journal Of Nursing Science Research, 2026)
Delayed detection of pediatric emergencies in emergency departments may increase the risk of clinical deterioration, intensive care admission, and mortality. The integration of the Pediatric Early Warning Score (PEWS) with nursing-based triage systems has emerged as a strategic approach to improve the accuracy of identifying emergency conditions in children. This study aimed to analyze the predictive performance of Nurse-Led Integrated PEWS–Triage Systems in detecting pediatric emergency conditions. A prospective analytical observational design was conducted at RS Islam Siti Khadijah Palembang from January to March 2026. A total of 48 pediatric patients were recruited using consecutive sampling. Data were collected through direct nurse observation during triage assessment using the Integrated PEWS–Triage instrument, including respiratory, cardiovascular, neurological, and triage category parameters.  Instrument validity was tested using Pearson Product Moment correlation (r > 0.361), and reliability showed a Cronbach’s alpha of 0.87.Data were analyzed using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and Receiver Operating Characteristic (ROC) analyses. The findings revealed that the Nurse-Led Integrated PEWS–Triage Systems demonstrated a sensitivity of 85.0%, specificity of 78.6%, PPV of 73.9%, NPV of 88.5%, and an Area Under the Curve (AUC) ROC value of 0.87, indicating good predictive performance in detecting pediatric clinical deterioration. However, the relatively small sample size represents a study limitation and the findings should therefore be interpreted cautiously. Nurse-Led Integrated PEWS–Triage Systems have the potential to serve as effective early detection tools to support clinical decision-making and optimize pediatric emergency nursing response.